Strategi Pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) Konveksi di Kota Semarang dalam Pasar Terbuka Masyarakat Ekonomi Asean (MEA) 2015 - Khoirul Lilabror (Universitas Diponegoro, 2017)
This research is motivated by the implementation of the Asean Economic Community in 2015 which makes the flow of goods, services and labor that goes into Indonesia is becoming increasingly easier, where the enactment of the Asean Economic Community in 2015 is an opportunity or challenge the perpetrators of SMEs confection in Semarang.The purpose of this study was to determine how the strategies used by SMEs confection in Semarang in the face of the open market the Asean Economic Community. This type of research is exploratory research. Its population is SMEs confection in Semarang with a sample of five respondents. Analysis of the data used in this research is descriptive analysis method.Based on the results of descriptive and analysis, it could be concluded that the strategy used by the perpetrators of SMEs confection in Semarang is to expand its business in terms of human resource management, marketing, finance, product quality, technology and infrastructure.Advice can be given to the perpetrators of SMEs confection is improvements venture capital and human resources and improve the quality of products, and market expansion so that the product can compete and is known in the broader market